Stroke Volume Measurements by Echocardiography and Ultrasonic Cardiac Output Monitor in Children: A Prospective Observational Cohort Study - Fremuth, Jiri; Huml, Michal; Pomahacova, Tereza; Kobr, Jiri; Kormunda, Stanislav; Sykora, Josef (Pediatric emergency care, 2023)
OBJECTIVES: Stroke volume (SV) and cardiac output monitoring is a cornerstone of hemodynamic assessment. Noninvasive technologies are increasingly used in children. This study compared SV measurements obtained by transcutaneous Doppler ultrasound techniques (ultrasonic cardiac output monitor [USCOM]), transthoracic echocardiography jugular (TTE-J), and parasternal (TTE-P) views performed by pediatric intensivists (OP-As) with limited training in cardiac sonography (20 previous examinations) and pediatric cardiologists (OP-Bs) with limited training in USCOM (30 previous examinations) in spontaneously ventilating children. METHODS: A single-center study was conducted in 37 children. Each operator obtained 3 sets of USCOM SV measurements within a period of 3 to 5 minutes, followed with TTE measurements from both apical and jugular views. The investigators were blinded to each other's results to prevent visual and auditory bias. RESULTS: Both USCOM and TTE methods were applicable in 89% of patients. The intraobserver variability of USCOM, TTE-J, and TTE-P were less than 10% in both investigators. The SV measurements by OP-As using USCOM, TTE-J, and TTE-P were 46.15 (25.48) mL, 39.45 (20.65) mL, and 33.42 (16.69) mL, respectively. The SV measurements by OP-Bs using USCOM, TTE-J, and TTE-P were 43.99 (25.24) mL, 38.91 (19.98) mL, and 37.58 (19.81) mL, respectively.The percentage error in SV with USCOM relative to TTE-J was 36% in OP-As and 37% in OP-Bs. The percentage error in SV with TTE-P was 33% relative to TTE-J in OP-As and 21% in OP-Bs. CONCLUSIONS: Our findings show that the methods are not interchangeable because SV values by USCOM are higher in comparison with the SV values obtained by TTE. Both methods have low level of intraobserver variability. The SV measurements obtained by TTE-P were significantly lower compared with the TTE-J for the operator with limited training in echocardiography. The TTE-P requires longer practice compared with the TTE-J; therefore, we recommend to prefer TTE-J to TTE-P for inexperienced operators.
Keywords: echokardiografie; Stroke Volume; ultrazvuk; Child; lidé; Monitoring, Physiologic; prospektivní studie; dítě; monitorování fyziologických funkcí; Prospective Studies; Cardiac Output; tepový objem; Ultrasonics; minutový srdeční výdej; Echocardiography; Humans